Carlo Battisti linguista e bibliotecario Studi e testimonianze - Stagi, Tiziana; Guerrini, Mauro; Parenti, Alessandro (Biblioteche & bibliotecari / Libraries & librarians, 2019)
Carlo Battisti (Trento 1882-Empoli 1977) was one of the major linguists in Italy and took part to the history of cinema starring in Vittorio De Sica's Umberto D.. His long and intense activity has been largely divided between linguistics and library science since the very beginning of his studies at the University of Vienna. In Florence, Battisti held lectures of Comparative History of the Romance Languages and of Library science and Bibliography at the School for Librarians and Palaeographer-Archivists, of which he was also director. The eight studies published here offer biographical and intellectual insights on him, and bring a series of unpublished documents to light. The volume is completed by an iconographic appendix.